Comparative analysis of the SolWat photovoltaic performance regarding different PV technologies and hydraulic retention times. (15th June 2021) - Pichel, N.; Vivar, M.; Fuentes, M.
Highlights: SolWat (PV + SODIS) electrical performance was evaluated regarding different HRT and PV technologies. SolWat thin film panels produced more energy than a single module at shorter HRT. Thin film black surface enhanced far infrared light absorption and heat favouring SODIS. No clear benefits were observed from shorter HRT in mono and multicrystalline panels. Thin film technology was found to be the most suitable technology for its integration into SolWat. Abstract: SolWat is a hybrid photovoltaic (PV) and photochemical technology, which integrating a PV module and a water disinfection reactor on top of it, was developed to meet the needs of safe drinking-water and electricity in developing countries. This paper assessed the effects of the water disinfection reactor on the electrical performance of the PV module integrated into the SolWat system regarding different hydraulic retention times (HRT) and PV technologies. With this aim, several tests were conducted outdoors under natural climatic conditions. Results showed that while no clear benefits were observed from the water disinfection reactor and reduced HRT on the electrical performance of both monocrystalline and multicrystalline technologies, the final energy output of a-Si thin film PV panels benefited from the cooling effect of water on its front surface being able to produce even more energy than a single PV panel when working at shorter HRT. In addition, the working module temperature was always lower when HRT was shorter; its efficiency under the diffuse light conditions created by the water disinfection reactor was better than monocrystalline and multicrystalline technologies; and its black surface enhanced the absorption of far infrared light and heat by the water disinfection reactor favouring higher water temperatures and thus higher disinfection rates. In conclusion, thin film PV technology is the most suitable to be integrated into the hybrid SolWat systems when comparing with monocrystalline and multicrystalline technologies.